Synergistic Effect of Quercetin Nanoparticles on Liver and Pancreas Tissues and Oxidative Stress of Streptozotocin-Induced Diabetic Rats - Abd El-Rahman, Soheir N.; Al-Jameel, Suhailah S. (Asian Journal of Chemistry, 2017)
Nanotechnology technique increases the solubility in water and bioavailability of drug. This study aimed to investigate the synergistic effects of quercetin nanoparticales (QUNPs) on a streptozotocin (STZ)-induced diabetic rats to determine their potential role in alleviating diabetes and its oxidative stress-induced. In this study, STZ-diabetic rats were treated with QUNPs (10 and 20 mg/kg bw/day) for 7 weeks to analyze their effects on lipid profile, markers of hepatic enzyme and enzymic antioxidant (MDA, SOD, GSH), also pancreas and liver tissues. The results of this study indicated that QUNPs (10 and 20 mg/kg bw/day) administrated rats down-modify hyperglycemia and oxidative stress. Furthermore, when treated diabetic rats with QUNPs (10 and 20 mg/kgbw/day) it is noticed a high significant improvement in histological structural degeneration of pancreas and liver. Quercetin nanoparticales (20 mg/kg bw/day) exhibited maximum inhibition of lipid profile, hepatic enzymes and oxidative stress, which indicates a protective role in the diabetic rats pancreas and liver. Present results show that the quercetin nanoparticles synergistic effects to improve hyperglycemia and oxidative stress in diabetic rats and so, open a new areas that can help to define a different trend on the developing of active treatments of nano-flavonoids.